Leucoféresis terapeútica para hiperleucocitosis en leucemia mieloide crónica: Therapeutic lukopheresis for hyperleukocytosis in chronic myeloid leukemia - Huerto Aguilar, José Luis (2024)
Chronic myeloid leukemia usually presents nonspecific symptomatology, but clinical signs of hyperleukocytosis appear when it progresses to the acute phase. We present a case of hyperleukocytosis associated with acute phase chronic myeloid leukemia that responds to treatment with leukopheresis. The use of this procedure is recommended to reduce symptomatology, but not as definitive treatment of the disease.